Problematika Implementasi Layanan Pencatatan Pernikahan melalui Aplikasi SIMKAH pada KUA Kabupaten Dharmasraya - Hendriyanto Hendriyanto; Nofialdi Nofialdi; Sri Yunarti; Iman Asroa B.S (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
The phenomenon of marriage registration that often occurs is related to the non-registration of marriages, marriage registration services which are often ignored and the existence of marriage registration services that are not carried out optimally. This study aims to describe the problems in implementing marriage registration services using SIMKAH at the KUA of Dharmasraya Regency. The research was conducted using a qualitative approach to field research. The research was carried out by going out into the field to conduct interviews with the heads of the KUA in Dharmasraya Regency to obtain data. Other data were obtained by studying the documentation of the marriage archive documents at the KUA. The findings were analyzed using the Spradley technique to analyze the general description of the application and the constraints that occur related to the registration of marriage services with SIMKAH. The findings explain that in general KUA in Dharmasraya District have all used SIMKAH in carrying out marriage administration services. The problems that occur are the lack of expert staff, the internet network is not stable, there are only one server in Indonesia which causes frequent server congestion and errors, as well as conventional ways of managing marriage administration.